Pemasangan Pompa Air Irigasi Bertenaga Surya Untuk Persawahan Masyarakat Desa Bangun Rejo Kab Kutai Kartanegara - Toyib; Suratno; Ipniansyah; Cornelius; Bella Cahya Ningrum (LPPM Universitas Battuta, 2025)
Solar energy has become one of the increasingly popular solutions to meet energy needs, especially in remote scenarios such as rural areas, Solar energy has become an increasingly profound focal point in the context of the modern world's energy needs. Water pumps have become a crucial element in meeting the water needs of humans, agriculture, industry, and society in general. Solar water pumping is a technology that has great potential to address the problem of water scarcity in community farms. By utilizing the abundant sunlight, these water pumps can make plant watering water more accessible, increase the productivity of farm gardens, reduce operational costs, and ultimately, increase the community's living rates. This research aims to install irrigation water pumps for the community of Bangun Rejo Village, Kutai Kartanegara Regency. The research method used is the experimental method by making a solar pump design. Data taken in the form of solar panel data, SCC data, battery data and water pump data. The description of the PLTS System Tool Design that will be designed Solar Powered Irrigation Water Pump has Main Components Namely Solar Modules, Solar charge controller, DC MCB, Battery and DC Water Pump. The results showed that the calculation and design of the solar power generation system for water pumps are in accordance with the needs and are able to function properly under actual conditions. The capacity and efficiency of the selected equipment support optimal system operation, ensuring the sustainability of energy supply for irrigation purposes.